رحلة البحث عن سبعين بدريا - الشيباني, سلطان بن مبارك (منشورات الوقف المبارك, 2024)
Keywords: Hadith

إشكالية تدوين الحديث: تاريخية حديث "الافتراق" وتمثله من الفرق الإسلامية - باروت, محمد جمال (مجلة أسطور للدراسات التاريخية, 2023)
Keywords: Hadith

منهج التخريج العلمي للحديث (دراسة تطبيقية) - حمدي, صالح بن محمد (الحياة, 2006)
Keywords: Hadith

Ibadi ahadith (Hajarmulder's Blog, 2008)
Ibadi Islam is mainly found in Oman and also in some places of eastern African countries like Somalia, further in Algeria, Tunisia and Libya. Ibadism’s founding figures are Jabir ibn Zayd and…
Keywords: Hadith

A Reappraisal of Ibāḍī Ḥadīth in Light of Ḍirār ibn ʿAmr’s Kitāb al-Taḥrīsh - Miah, Azaher (Panel 65 reconsidering Kharijism in early Islamic history, 2017)
Keywords: Hadith

Ibāḍi Ḥadīth: an Essay on Normalization - Wilkinson, John Craven (Der Islam, 1985)
A detailed study of Ibāḍī Ḥadīth works in the West and in the East, with an investigation into the possible sources of Abū Yaʿqūb Yūsuf b. Ibr. al-Warjlānī’s Tartīb of the Musnad (or the Ṣaḥīḥ) of al-Rabīʿ b. Ḥabīb al-Farāhīdī. After an introduction around al-Rabīʿ b. Ḥabīb’s Musnad (231-235), follow: The Omani sources (236); The Maghribi sources (240); The Āthār of al-Rabīʿ (241); The Dīwān Jābir b. Zayd (245); Ibāḍī normalization: the historical background (246); Early Mashriqi treatises in the Maghrib: the Mudawwana and the K. Abī Sufyān (247); The historical normalization process (252); Early rationalization of Fiqh (253). At the end of his article Wilkinson says that Ibāḍī law was only made to conform at a relatively late date to the orthodox schools. He hopes to have cleared some of the overlay which the Ibāḍīs themselves developed upon their original school to show that there are important traces of its early development to be found in their written records. The Ḥadīth collection is not part of that genuine early Ibāḍī material. (See Wilkinson 1987b, 153-154).
Keywords: Hadith